Optimization of Regeneration Protocol and Agrobacterium Mediated Transformation in Carnation (Dianthus caryophyllus L.) - H M Kallesh Prasad; J B Mythili; Tejaswini .; Lalitha Anand; H J Rashmi; C Suneetha (Journal of Horticultural Sciences, 2009)
An efficient and reproducible regeneration protocol for carnation genotypes Arka Flame and IIHRS-1 has been developed from leaf and stem explants. Although IIHRS-1 showed slightly higher regeneration (55%) compared to Arka Flame (49.2%), there was no significant difference in their regeneration response. However, significant difference in regeneration potential was observed with leaf explant exhibiting higher regeneration potential (5.5 shoots/explant) as compared to (4.9) stem explant. Among various plant growth regulator combinations tested for regeneration, the best regeneration response and maximum regeneration potential was obtained in MS medium supplemented with NAA (0.1 mg/l) and TDZ (1.0mg /l) for both the explants and genotypes used. The medium also proved suitable for inducing elongation of regenerated shoots. Rooting of in vitro formed shootlets could be induced at greater frequency in MS medium supplemented with IAA (1.0 mg/l). Based on this protocol, transformation was carried out in genotype IIHRS-1 using leaf explants with Agrobacterium tumefaciens LBA 4404 with binary vector pROK2 containing baculovirus chitinase gene under the control of 35S promoter with npt II serving as selectable marker. There was regeneration of putative transformants at a frequency of 28.9%. However, great difficulty was encountered in rooting of shoots. Hence a few shoots regenerated on selection medium at random were tested for transgene integration. Out of the three shoots tested for npt II amplification, two shoots tested positive. The presence of transgene was confirmed through PCR amplification of npt II gene and dot blot analysis of chitinase gene.